2013
DOI: 10.1016/j.virol.2013.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a blocking enzyme-linked immunosorbent assay (ELISA) to differentiate antibodies against live and inactivated porcine reproductive and respiratory syndrome virus

Abstract: The aim of this study was to establish a method that could differentiate antibodies against live and inactivated vaccines of porcine reproductive and respiratory syndrome virus (PRRSV). A blocking ELISA (b-ELISA) was established using the PRRSV non-structural protein, Nsp9, as the antigen and a monoclonal antibody, 2D6, against the Nsp9 protein as the capture antibody. The test was validated by using 415 clinical sera in the b-ELISA compared to a commercial kit based on the indirect ELISA using the nucleocapsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…This confirms the findings of another study, where no antibody response was detected with the IDEXX ELISA after inactivated PRRSV vaccination as well [10]. As expected from the results of other studies [2, 6, 16], the IDEXX ELISA tested most piglets PRRSV Ab positive from day 10 after infection onwards. According to a study by Zuckermann et al, the IDEXX ELISA was able to detect higher S/P values in pigs pre-vaccinated with an inactivated PRRSV vaccine than in non-vaccinated pigs on days 7 and 10 after the subsequent challenge [13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This confirms the findings of another study, where no antibody response was detected with the IDEXX ELISA after inactivated PRRSV vaccination as well [10]. As expected from the results of other studies [2, 6, 16], the IDEXX ELISA tested most piglets PRRSV Ab positive from day 10 after infection onwards. According to a study by Zuckermann et al, the IDEXX ELISA was able to detect higher S/P values in pigs pre-vaccinated with an inactivated PRRSV vaccine than in non-vaccinated pigs on days 7 and 10 after the subsequent challenge [13].…”
Section: Discussionsupporting
confidence: 91%
“…In one study using serum samples collected from challenged pigs, a sensitivity of 100% was found [5]. Measured with the IDEXX ELISA, an antibody response can be detected beginning between days 9 and 12 after PRRSV infection or vaccination with attenuated PRRSV live vaccines [2, 69] and lasting at least until day 120 after vaccination or challenge [10]. Although the application of certain inactivated PRRSV vaccines seems to prime the immune system and can, according to some studies, lead to a faster and more effective immune response after PRRSV infection [11, 12], no antibody response has been observed with the IDEXX ELISA after vaccination with inactivated PRRSV vaccines [10, 13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nsps are synthesized when the virus is replicating, so healthy animals that are vaccinated with inactivated virus would only be expected to elicit antibodies to structural proteins, so the anti-Nsp antibodies in animal serum is a clear indication of virus activity [24] . Among the nonstructural genes of PRRSV, Nsp9 contained within ORF1b is the most conserved region of Arteriviridae genomes and encodes RdRp.…”
Section: Discussionmentioning
confidence: 99%